2008
DOI: 10.1021/bm701269p
|View full text |Cite
|
Sign up to set email alerts
|

Humicola insolens Cutinase-Catalyzed Lactone Ring-Opening Polymerizations: Kinetic and Mechanistic Studies

Abstract: This paper explores reaction kinetics and mechanism for immobilized Humicola insolenscutinase (HIC), an important new biocatalyst that efficiently catalyzes non-natural polyester synthetic reactions. HIC, immobilized on Lewatit, was used as catalyst for epsilon-caprolactone (CL) and omega-pentadecalactone (PDL) ring-opening polymerizations (ROPs). Plots of percent CL conversion vs time were obtained in the temperature range from 50 to 90 degrees C. The kinetic plot of ln([M]0/[M]t) vs time (r2 = 0.99) for HIC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…A large increase in FNL activity for -caprolactone polymerization was found when the reaction temperature increased from 60 • C to 90 • C. After 72 h, the monomer conversion increased from 76% at 60 • C to almost 100% at 90 • C. The increased monomer conversion values at higher temperatures were probably caused by the decreased diffusion constraints in the reaction mixture and increased water molecules accessible in the chain initiation reaction. Compared with the complete loss of enzymatic activity of HIC at temperatures more than 70 • C [31], FNL was highly thermostable, and could efficiently catalyze the ring-opening polymerization of -caprolactone at much higher temperatures. This would be of great significance for the simultaneous, single-step chemoenzymatic synthesis of novel polymers.…”
Section: Effect Of Reaction Time and Temperaturementioning
confidence: 99%
“…A large increase in FNL activity for -caprolactone polymerization was found when the reaction temperature increased from 60 • C to 90 • C. After 72 h, the monomer conversion increased from 76% at 60 • C to almost 100% at 90 • C. The increased monomer conversion values at higher temperatures were probably caused by the decreased diffusion constraints in the reaction mixture and increased water molecules accessible in the chain initiation reaction. Compared with the complete loss of enzymatic activity of HIC at temperatures more than 70 • C [31], FNL was highly thermostable, and could efficiently catalyze the ring-opening polymerization of -caprolactone at much higher temperatures. This would be of great significance for the simultaneous, single-step chemoenzymatic synthesis of novel polymers.…”
Section: Effect Of Reaction Time and Temperaturementioning
confidence: 99%
“…For example, it has been reported that the polymerization of -caprolactone using Novozym 435 in toluene at 70 • C for 4 h produced poly(-caprolactone) with an isolated yield of 85% and a number-average molecular weight (Mn) of 44,800 g/mol [13]. Recently, a novel cutinase from H. insolens was explored with promising polyester synthesis activity, with Mn value of the synthesized poly(-caprolactone) of 24,900 g/mol at 70 • C for 24 h [15,17]. Despite these impressive results, enzymatic polymerization remains in the research and development stage, in part due to the high cost of producing and immobilizing these lipases.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalides and their analogs have shown interesting biological activities including antifungal and cytotoxic activities (11,12). These lactones also have potential utility in polymer chemistry as they make interesting substrates for ring opening polymerization of lactones to polyesters (13,14). One possible explanation could be the initial formation of a monoaldehyde that reacts with the intramolecular hydroxymethyl group to form a hemiacetal that is then oxidized to the observed lactone (Scheme 4).…”
Section: Scheme 3 Proposed Mechanism For the Pcc Catalyzed Oxidationmentioning
confidence: 99%